PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Mahasiswa Pengguna Produk Sepatu Merek Converse di Fisip Universitas Merdeka Malang) - Supriyadi Supriyadi; Yuntawati Fristin; Ginanjar Indra K.N (Jurnal Bisnis dan Manajemen, 2017)
This research is motivated by intense competition manufacturing industries that produce shoes. And how the company in setting the direction and goals of the sales of products that will be offered. This study aimed to describe (1) If the variable influence on product quality product purchasing decisions Converse brand shoes. (2) Wheter variables affect the brand image of the product purchase decisions Converse brand shoes. (3) Is the variable product quality and brand image influence the purchasing decisions Converse brand shoes. The populations in this study were students Converse brand shoes product users in the Faculty of Social and Political Science at the Merdeka University of Malang, a total of 39 respondents using non-probability sampling (sampling satured). Data that has met the validity and raliability, and classical assumption (t test and F test) is processed to produce a regression equation as follows: Y= 13,789 + -0,261X1 + 0,689X2 Where the purchasing decisions variable (Y), the qulity of the product (X1), and brand image (X2). Hypotesis testing using t test showed that the variable qulity of the products that have been researched proved no effect on the purchasing decisions, but the variables that proved influential brand image on consumers purchasing decisions.Hypotesis testing using the F test shows that the variable quality of the product and brand image influence on purchase decisions by 22,7%, while the remaning 77,3% is influenced by variables that are not used in this study.